The Impact of Hospitalization for Acute Myocardial Infarction on Adherence to Statins Among Older Adults - Kronish, Ian M. (Circ Cardiovasc Qual Outcomes, 2016)
BACKGROUND: Little is known about the impact of hospitalization for an acute myocardial infarction (AMI) on subsequent adherence to statins. METHODS AND RESULTS: Using administrative claims from a 5% random sample of Medicare beneficiaries, we identified a cohort of Medicare patients ≥65 years, hospitalized from 2007–2011, taking statins in the year before AMI hospitalization (n=6,618). We then determined the proportion of patients nonadherent to statins (proportion of days covered [PDC] <80%) in the year before AMI hospitalization who became statin adherent (PDC ≥80%) in the year after AMI hospitalization. The proportion of statin adherent patients who became nonadherent was also studied. These proportions were compared with patients hospitalized for pneumonia (n=11,471) and patients not hospitalized (n=158,099) in 2010 and 2011. Among patients nonadherent to statins before AMI hospitalization, 37.7% became adherent after discharge. Patients hospitalized for AMI were more likely to become adherent than patients hospitalized for pneumonia (aRR 1.70, 95%CI 1.57–1.84) or patients not hospitalized (aRR 1.79, 95%CI 1.68–1.90). Among patients adherent to statins before AMI hospitalization, 32.6% became nonadherent after discharge. Those hospitalized for AMI were less likely to become nonadherent than those hospitalized for pneumonia (aRR 0.93, 95%CI 0.88–0.98) but more likely to become nonadherent than patients without hospitalizations (aRR 1.41, 95%CI 1.35–1.48). CONCLUSIONS: Among nonadherent patients, hospitalization for AMI was associated with increased likelihood of becoming adherent to statins compared to hospitalization for pneumonia or no hospitalizations. Among adherent patients, hospitalization for AMI was associated with increased likelihood of becoming nonadherent to statins compared to no hospitalizations.